2023
DOI: 10.3390/biomedicines11071873
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Mitochondrial Oxygen Tension during Red Blood Cell Transfusion in Chronic Anemia Patients: A Pilot Study

Abstract: In light of the associated risks, the question has been raised whether the decision to give a blood transfusion should solely be based on the hemoglobin level. As mitochondria are the final destination of oxygen transport, mitochondrial parameters are suggested to be of added value. The aims of this pilot study were to investigate the effect of a red blood cell transfusion on mitochondrial oxygenation as measured by the COMET device in chronic anemia patients and to explore the clinical usability of the COMET … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…In this experiment, hemodilution in pigs resulted in an earlier decrease in the cutaneous mitoPO 2 compared to the NIRS tissue oxygenation saturation measurements (StO 2 ) (15). Second, a recent pilot study in chronic anemia patients (16) has shown variable individual responses to cutaneous mitoPO 2 measurements during red blood cell transfusion. This further supports the potential of cutaneous mitoPO 2 measurements to provide an insight into tissue oxygenation.…”
Section: Introductionmentioning
confidence: 74%
“…In this experiment, hemodilution in pigs resulted in an earlier decrease in the cutaneous mitoPO 2 compared to the NIRS tissue oxygenation saturation measurements (StO 2 ) (15). Second, a recent pilot study in chronic anemia patients (16) has shown variable individual responses to cutaneous mitoPO 2 measurements during red blood cell transfusion. This further supports the potential of cutaneous mitoPO 2 measurements to provide an insight into tissue oxygenation.…”
Section: Introductionmentioning
confidence: 74%